2016
DOI: 10.1051/0004-6361/201526371
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar diffusion in low-mass star formation

Abstract: Angular momentum transport and the formation of rotationally supported structures are major issues in our understanding of protostellar core formation. Whereas purely hydrodynamical simulations lead to large Keplerian disks, ideal magnetohydrodynamics (MHD) models yield the opposite result, with essentially no disk formation. This stems from the flux-freezing condition in ideal MHD, which leads to strong magnetic braking. In this paper, we provide a more accurate description of the evolution of the magnetic fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
277
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(312 citation statements)
references
References 53 publications
35
277
0
Order By: Relevance
“…The first type of simulations are identical and/or similar to the ones performed in Masson et al (2016). They have an initial core mass of 1 M , a uniform density profile and a uniform magnetic field with a mass-to-flux over critical mass-to-flux ratio of 2 or 5.…”
Section: Dependence Of the Disc Radiusmentioning
confidence: 99%
“…The first type of simulations are identical and/or similar to the ones performed in Masson et al (2016). They have an initial core mass of 1 M , a uniform density profile and a uniform magnetic field with a mass-to-flux over critical mass-to-flux ratio of 2 or 5.…”
Section: Dependence Of the Disc Radiusmentioning
confidence: 99%
“…Even when the magnetic field in the cloud core is relatively strong (e.g., when its mass-to-flux ratio normalized by the critical mass-to-flux ratio is on order of unity), a gravitationally unstable disk can form during the Class 0/I YSO phase. Indeed, recent three-dimensional non-ideal magnetohydrodynamics (MHD) simulations suggest that even with a relatively strong magnetic field, a circumstellar disk forms immediately after protostar formation Tomida et al 2015;Tsukamoto et al 2015aTsukamoto et al , 2015bMasson et al 2016;Wurster et al 2016) and becomes gravitationally unstable Tsukamoto et al 2015aTsukamoto et al , 2015b; for a review of disk formation in magnetized cloud cores, see Tsukamoto 2016). In particular, Machida et al (2011) investigated the long-term evolution of circumstellar disks (until 10 5 years after protostar formation) and showed that gravitationally unstable disks can form even in strongly magnetized cloud cores.…”
Section: Introductionmentioning
confidence: 99%
“…and resolution. The development of a disk might start right after protostar formation (Inutsuka et al 2010;Machida & Matsumoto 2011;Tsukamoto et al 2015), or a rotationally supported structure corresponding to the first core, or surrounding it, might exist before protostar formation (Inutsuka et al 2010;Machida & Matsumoto 2011;Tsukamoto et al 2015;Joos et al 2012;Tsukamoto & Machida 2013;Masson et al 2016). Observations that can test these predictions are needed in order to better understand the formation of protostars and their evolution.…”
Section: Introductionmentioning
confidence: 99%